البنية المنطقية لتصميم وحدات الإقامة في المجمعات السياحية في الساحل السوري - أرمنازي زينة (Latakia University Journal -Engineering Sciences Series, 2019)
تعتبر وحدات الإقامة العمود الفقري للسياحة حيث تعتمد هذه النوعية من الخدمات على توفير أنواع و مستويات متعددة لتلبي رغبات و إحتياجات السائحين المختلفة وقد شهدت السياحة السورية تطوراً كبيراً على مستوى القدوم السياحي وجودة الخدمات ونمو الاستثمارات السياحية وإبراز الصورة الحضارية لسورية وبهدف زيادة الطاقة الاستيعابية ونمو المنتج السياحي المحلي كان لابد من دراسة تحليلية لمجمعاتنا السياحية وفق تدرج هرمي منطقي ومنه خص البحث وحدات الإقامة في المجمعات السياحية لما تقدمه من راحة للسياح . وبناءً عليه كان لابد من تحديد الميزات الاساسية لوحدات الإقامة والاسس التي وجهت عمل الباحثين لمواجهة مشكلة الوصول لأسس تصميمية معمارية وعمرانية تنظيمية لوحدات الإقامة وبناء عليه يقدم البحث قوام البنية المنطقية لتصميم وحدات الإقامة في المجمعات السياحية من منظار شمولي وبتدريج علمي يعتمد على خمس خطوات يقدمها البحث لتكون أساس لبناء المنظومة الخاصة بوسائل الإقامة كلها لتحقيق الراحة للسياح بهدف التقييم المستمر للتجارب السياحية. Accommodations are the backbone of the tourism considered where this quality of service depends on the types and provide multiple levels to meet the wishes and needs of different tourists. Syrian tourism has seen a significant at the level of tourist arrival and the quality of services and the growth of tourism investments and to highlight the civilized image of Syria. , in order to increase the capacity and growth of the local tourism product has to be analytical study of our complexes tourism according to hierarchy and it singled Find Accommodations in the tourist complexes for its comfort for tourists And, it was necessary to identify the key features of accommodation units and foundations that guided the work of researchers to address the problem of access to the foundations of design architectural and urban organizational units residence Accordingly Find strength of the logical structure to design and Accommodations in tourist complexes from a holistic perspective offers Scale scientific relies on five steps provided by research to be the basis for building the system for the whole house means to bring the convenience of touristsin order to continuous assessment of tourist experiences .